Evaluation of anticancer, antioxidant activity and phenolic compounds of Artemisia absinthium L. Extract - Koyuncu, Ismail (Cellular and Molecular Biology, 2018)
In the treatment of cancer, which remains a fatal disease, increasingly successful treatment rates of alternative therapies using the power of plants have directed the scientific world towards natural plant resources. This study aimed to examine the anti-cancer and antioxidant properties and identify the phenolic content of the methanolic extract obtained from Artemisia absinthium L. (AR) species, which is used as folk-medicine. The antioxidant activity of the extract was investigated using total phenolics, flavonoids, ABTS and CUPRAC methods. Phenolic component analysis of the plant extract was performed by LC-MS/MS. The anti-cancer property of AR extract was investigated on human colon (DLD-1), endometrium (ECC-1) cancer cells and embryonic kidney (HEK-293) cells. Cytotoxic effects were defined with MTT, apoptotic activity with DNA fragmentation ELISA and AO/EB fluorescent staining, the genotoxic effect with the comet assay and the intracellular oxidative status with TAS and TOS methods. As a result of the study, it was determined that AR extract showed an antioxidant effect, and as a result of the content analysis made with LC-MS/MS, phenolic components were determined, the most abundant being chlorogenic acid, followed by quinic acid, cinnamic acid, rhoifolin and malic acide. AR extract showed cytotoxic activity on DLD-1 and ECC-1 cancer cells, while the cytotoxic effect on HEK-293 cells was determined to be low. It was determined that by increasing the intracellular amount of free radicals on cancer cells, this led to DNA damage, which consequently led to apoptosis of the cancer cells.